Application of Modern Teaching Methods through the Supply Chain Strategy and Integrated Curriculum - Nourabadi, Soolmaz (ExcelingTech, 2020)
Abstract This article examines the relation of integrated curriculum with implementation of modern teaching methods through the supply chain strategy in education. The research method in this article is analytical-deductive. Considering the fact that in order to extract the dimensions of integrated curriculum, its analysis is done in terms of effective factors in the integration of the curriculum, the research method is an analytical type, and considering that the relation between the integrated curriculum and the application of modern teaching methods is examined, it is deductive. The results show that the nature of integrated curriculum, coherence of students' learning in order to learn has been more effective. The main advantages of it includes: Actualization of learners' talents, training creative and critical thinking, problem solving, and, strengthening research oriented. The nature of modern teaching methods indicates the active role and personal experience of learner, the interactive process of learning in order to independence, social adjustment, team working skill, social skill, and, comprehensive analysis. So integrated curriculum by removed barriers restricted of subject-based curriculum such as predetermined content, limited questions, lack of relationship of achieved knowledge with life and lack of interdisciplinary relation requires modern methods to be successful in growing scientific search skill, referring to numerous sources, consultation and participation of learners.